Explain Leibniz's Approach to Solving the Problem of Evil - Masoumeh RajabNezhadian ,Abdullah HosseiniEskandian, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The problem of evil is one of the cases that has always occupied man throughout the history of thought and has been confronted with various explanations by religious thinkers.Leibniz is one of the thinkers who has tried to explain the problem of evil in a way that does not contradict the existence of God and also the goodness of the world of creation.Explaining the problem of evil in Leibniz's thought and getting acquainted with his solutions for explaining the problem of evil, in addition to introducing us to his thoughts on it, can be the answer to many questions about the problem of evil.In this article, an attempt is made to study what evil is, the types of evil and the solutions to the problem of evil in Leibniz's thought by using descriptive-analytical method and using library resources.Leibniz not only does not consider evil to be in conflict with theism, but also believes that by understanding it correctly, we can believe more in the existence of God.